2017
DOI: 10.1051/0004-6361/201731306
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a repeated transit signature in the light curve of the enigma star KIC 8462852: A possible 928-day period

Abstract: As revealed by its peculiar Kepler light curve, the enigmatic star KIC 8462852 undergoes short and deep flux dimmings at a priori unrelated epochs. It presents nonetheless all other characteristics of a quiet 1 Gyr old F3V star. These dimmings resemble the absorption features expected for the transit of dust cometary tails. The exocomet scenario is therefore most commonly advocated. We reanalyzed the Kepler data and extracted a new high-quality light curve to allow for the search of shallow signature of single… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…A similar idea was presented earlier in [131]. The authors identified two strikingly similar events in the Kepler light curve which are approximately 0.1% deep and occurred at D216 and D1144.…”
Section: The Lord Of the Ringssupporting
confidence: 78%
“…A similar idea was presented earlier in [131]. The authors identified two strikingly similar events in the Kepler light curve which are approximately 0.1% deep and occurred at D216 and D1144.…”
Section: The Lord Of the Ringssupporting
confidence: 78%
“…This work recovered the events discovered by Rappaport et al (2018), found one more around HD 182952, and argued that the host stars are likely young (∼100Myr old). For completeness, we note that the deep and irregular dimming events seen towards KIC 8462852 have also been interpreted as having a cometary origin (Boyajian et al 2016;Wyatt et al 2018;Kiefer et al 2017), although the shape and depth of these events are very different to those discovered by Rappaport et al (2018) and Kennedy (2018).…”
Section: Introductionmentioning
confidence: 80%
“…KIC 8462852's variability manifests itself as asymmetric drops in brightness of up to 22%, many of which last several days (the "dips"). There is little or no sign of periodicity in the four years of Kepler observations (but see Kiefer et al 2017). Additionally, the duty cycle of the dips is low, occurring for less than 5% of the four-year period Kepler observed it.…”
Section: Introductionmentioning
confidence: 94%